Improving the mechanical and thermal properties of chlorinated poly(vinyl chloride) by incorporating modified CaCO3 nanoparticles as a filler - Abd El-Hakim, Abou El fettouh Abd El Moneim; Haroun, Ahmed Abd Allah; Rabie, Abdel Gawad Mohamed; Ali, Gomaa A. M.; Abdelrahim, Mohamed Yahia Marei (TÜBİTAK, 2019)
Chlorinated poly(vinyl chloride) (CPVC)/calcium carbonate nanocomposites were successfully prepared by the incorporation of calcium carbonate (CaCO3) nanoparticles into the CPVC matrix. The compatibility between the two phases was obtained by surface modification of the CaCO3 nanoparticles with stearic acid, leading to improved material performance. The effects of the addition of different amounts of CaCO3 nanoparticles to the CPVC on the thermal, mechanical, and morphological characteristics of the CPVC/CaCO3 nanocomposites were investigated. The thermal stability of the CPVC/CaCO3 nanocomposites was evaluated by thermogravimetric analysis and differential scanning calorimetry. In addition, the surface texture of the CPVC and the dispersion of the CaCO3 were evaluated using scanning electron microscopy. Important enhancements in the thermal and mechanical properties of the modified CPVC/CaCO3 nanocomposites were obtained by incorporating different amounts (2.00%, 3.75%, and 5.75%) of surfacemodified CaCO3 nanoparticles within the CPVC polymer matrix. The results reveal that 3.75% of CaCO3 was the optimum amount, where the CPVC/CaCO3 nanocomposite shows the highest impact strength, the highest tensile strength, the highest thermal stability, and the lowest elongation percentage.Replacement of the commercial impact modifier used in industry with the prepared surface-modified CaCO3 nanoparticles for the development of CPVC was successfully achieved.